2017
DOI: 10.1021/acsami.7b10010
|View full text |Cite
|
Sign up to set email alerts
|

Face-to-Face Interfacial Assembly of Ultrathin g-C3N4 and Anatase TiO2 Nanosheets for Enhanced Solar Photocatalytic Activity

Abstract: Face-to-face interfacial assembly of TiO-g-CN hybrid (2D TCN-A) is developed by surfactant-assisted hydrothermal treatment forming a sandwich structure of anatase TiO nanosheets (TiO-A, 5-6 monolayers) and g-CN nanosheets (∼3 monolayers). Post air-annealing is found effective for insertion of oxygen to the hybrid, which remedies the oxygen vacancies of TiO (B) nanosheets and converts it to anatase nanosheets. The enhanced light adsorption, increased donor density, and prolonged life of charge carries are achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 163 publications
(76 citation statements)
references
References 54 publications
3
73
0
Order By: Relevance
“…When both g‐C 3 N 4 and TiO 2 are reduced to nanosheets, the intimate and larger contact area between them further improves the rate of electron–hole separation. Moreover, as Figure a shows, the interfacial interaction also reduces the bandgap of TiO 2 in the surface‐to‐surface heterojunction from 3.3 to 2.91 eV, extending the light absorption range of TiO 2 nanosheets …”
Section: Interactions Between 2d Tmos and Substrates/2d Materialsmentioning
confidence: 95%
See 2 more Smart Citations
“…When both g‐C 3 N 4 and TiO 2 are reduced to nanosheets, the intimate and larger contact area between them further improves the rate of electron–hole separation. Moreover, as Figure a shows, the interfacial interaction also reduces the bandgap of TiO 2 in the surface‐to‐surface heterojunction from 3.3 to 2.91 eV, extending the light absorption range of TiO 2 nanosheets …”
Section: Interactions Between 2d Tmos and Substrates/2d Materialsmentioning
confidence: 95%
“…a) Photogeneration of H 2 over 2D TiO 2 ‐g‐C 3 N 4 nanosheets with the initial g‐C 3 N 4 dosage of 70 (2D TCN‐A‐70) and anatase TiO 2 nanosheets (TiO 2 ‐A) photocatalysts under UV−vis light irradiation. Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Interactions Between 2d Tmos and Substrates/2d Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anchoring of active semiconductors on g‐C 3 N 4 to form heterojunctions has been extended to a variety of inorganic substances. On account of the staggered band alignment between TiO 2 and g‐C 3 N 4 , a complementary and synergetic effect could be expected, once the two are hybridized into heterostructures . A few studies have focused on utilizing TiO 2 ‐g‐C 3 N 4 hybrids for microorganism removal.…”
Section: Graphitic Carbon Nitride (G‐c3n4)‐based Photocatalysts For Wmentioning
confidence: 99%
“…On account of the staggered band alignment between TiO 2 and g-C 3 N 4 , a complementary and synergetic effect could be expected, once the two are hybridized into heterostructures. 36,[88][89][90] A few studies have focused on utilizing TiO 2 -g-C 3 N 4 hybrids for microorganism removal. Li et al first demonstrated the use of TiO 2 -g-C 3 N 4 photocatalyst in antibacterial field.…”
Section: Graphitic Carbon Nitride (G-c 3 N 4 )-Based Photocatalysts Fmentioning
confidence: 99%